Pollen morphology of the Polish species of the genus Sorbus L. - Leszek Bednorz; Irmina Maciejewska; Dorota Wrońska-Pilarek; Toshiyuki Fujiki (Acta Societatis Botanicorum Poloniae, 2011)
This paper presents the results of the study on pollen morphology of five Polish species of the genus Sorbus L. (S. aria (L.) Crantz, S. aucuparia L. Emend. Hedl., S. chamaemespilus (L.) Crantz, S. intermedia (Ehrh.) Pers. and S. torminalis (L.) Crantz). Observations were carried out with light and scanning microscopes. Investigated pollen grains were small or medium size, most often subprolate or prolate spheroidal in outline. Exine of medium thickness, consisted of two layers. Mainly 3-zonocolporate or sometimes 4-zonocolporate (S. chamaemespilus and S. torminalis) grains were noted. Usually striatae type of sculpture was observed, except the grains of S. intermedia, which were characterized by intermediate type of sculpture, with the features both striate and regulate ornamentation. Pollen morphology of the investigated Sorbus species corresponds with their systematic classification. It is relatively easy to separate pollen grains of the following subgenera: Sorbus, Chamaemespilus and Torminaria. Only subgenus Aria includes grains of different morphology and therefore it is impossible to determine the diagnostic features of this subgenus. Pollen morphology does not confirm a close relationship between S. aria and S. intermedia. It is possible to distinguished pollen grains of all the analysed native species. However, there are no important differences in pollen morphology between the subspecies of Sorbus aucuparia. The key for Polish Sorbus species, based on pollen grain characters is given too.